Unequal ageing : the untold story of exclusion in old age - Cann, Paul; Dean, Malcolm (Policy Press, 2009)
This much-needed book analyses money, health, place, quality of life and identity, and demonstrates the gaps of treatment and outcomes between older and younger people, and between different groups of older people. It provides strong evidence of the scale of current disadvantage in the UK and suggests actions that could begin to change the picture of unequal ageing.